2020
DOI: 10.1177/0954406220905858
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the tribological behavior of functionally gradient iron-based brake pad material

Abstract: In this study, a functionally gradient iron-based brake pad material was developed and the tribological behavior was studied. The functionally gradient specimen had more copper near the base plate and more abrasives towards the top, which provides excellent joint strength and serves the purpose of braking, respectively. The layers had a hybrid composition of metallic materials (Fe, Cu), and abrasives (silicon carbide and aluminum oxide) to improve the strength, wear resistance, and toughness. Graphite was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Copper was added to achieve the liquid phase sintering of the specimens. [12][13][14] The powders were weighed accurately in a precision balance having readability of 0.0001 g. Based on the literature 12,15 and our prior experimental work, fly ash was effectively liquid phase sintered with 5% Cu. Two samples were fabricated and named as FA01 (Fly ash þ 5%Cu) sintered under normal (air) environment and other as FA02 (Fly ash þ 5%Cu) sintered under argon atmosphere.…”
Section: Liquid Phase Sintering Of Fly Ashmentioning
confidence: 99%
“…Copper was added to achieve the liquid phase sintering of the specimens. [12][13][14] The powders were weighed accurately in a precision balance having readability of 0.0001 g. Based on the literature 12,15 and our prior experimental work, fly ash was effectively liquid phase sintered with 5% Cu. Two samples were fabricated and named as FA01 (Fly ash þ 5%Cu) sintered under normal (air) environment and other as FA02 (Fly ash þ 5%Cu) sintered under argon atmosphere.…”
Section: Liquid Phase Sintering Of Fly Ashmentioning
confidence: 99%
“…At the core of an FGM disc, the material is steel to maintain structural rigidity, which gradually changes along the thickness and approaches purely ceramic at the friction surfaces to resist the severe thermal loading [ 5 , 11 ]. This significantly improves the thermomechanical behavior of the brake system as a whole [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While modern materials for friction pads in brake systems are usually composites, the proportion of individual components can also be changed along with the distance from the friction surface. Experimental investigations have shown that functional variations in the properties of the pad material significantly improve their braking characteristics [ 12 , 30 ]. In particular, the results have indicated that the wear resistance of a specimen made of a functionally graded material is higher than the wear resistance of its analogue made of a homogeneous material [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During braking, performance of these components in terms of efficiency, service life, and dissipation of heat from the contact surface depends on the operating conditions and material properties. It has been shown that the operating characteristics of the entire assembly of the braking system can be significantly improved by introducing a smooth gradient in the microstructure of the friction materials [ 1 ]. Such functionally graded materials (FGMs) are a class of heterogeneous materials with continuous variation of properties over their volume.…”
Section: Introductionmentioning
confidence: 99%